Prediction of design loads for deep water subsea lifting operations based on non-stationary time response. (November 2020) - Tommasini, Rodrigo Batista; Pavanello, Renato; Carvalho, Leonardo de Oliveira
Abstract: Two methodologies for the prediction of the design loads of deep water subsea lifting operations crossing resonance zones are presented. These methodologies are applicable to models that consider the influence of the payout speed on the dynamics of the operation, leading to a non-stationary time series for the dynamic forces on the system. The first model is based on running several random simulations of the same scenario and using these simulations as a sample in which statistical parameters are inferred. The second model uses a weighted least squares approach to predict a normalizing function that is used to evaluate the statistical parameters of the response. Both models are tested by considering the installation of a typical manifold in the Pre-Salt fields, in Brazil, and are able to predict the general form of the envelope of forces on the cable for various sea states and payout speeds. The models also provided similar results for the availability of the vessel after evaluating the weather window for this operation. Finally, the advantages of using the weighted least squares approach in comparison to the direct method are discussed, since it may considerably reduce the total number of simulations required to perform a real operation assessment, especially during preliminary design phases. Highlights: Two methodologies are presented to evaluate the design loads of deep water subsea lifting operations. The methodologies estimate the maximum loads on the system via non-stationary time series. The first is based on obtaining the statistics of the response by running several random simulations for the same scenario. The second uses a weighted least squares technique to predict the loads by using few random simulations for a given scenario. Both methodologies present similar results; but one of them is considered more reliable, and the other faster.